Educational Innovation in Adult Learning Considering Digital Transformation for Social Inclusion - Abdon Ramirez; Esteban Inga (MDPI AG, 2022)
This research seeks to identify teaching-learning mechanisms that allow innovation and educational evolution for Youth and Adult Basic Education and thus achieve social inclusion in a rural development environment that has technological limitations and internet access in rural areas. The work seeks to identify a strategic process of learning objects to apply an inverted classroom in no presential modality. The objective is to respond to the low level of knowledge in the area of Language and Literature to mitigate the lack of understanding of the andragogical resources of the teachers in virtual classes. A methodological strategy is proposed that is related to the scientific field through bibliometric and quantitative analysis based on scientific information; in a second moment, the environment is evaluated via satisfaction surveys conducted with students and teachers of the third baccalaureate of the rural areas in the no presential modality of the Juan Jiménez Educational Unit, Abdón Calderón extension, province of Sucumbíos, Ecuador. A total of 66.67% of teachers between 41 and 45 agree with implementing ICT as a strategy for better learning in the education of young people and adults despite the scarce access to the internet in rural areas.